Effectiveness of structured teaching programme on knowledge and practice regarding prevention of nosocomial infection among staff nurses - Bhattacharyya, Srabanti; Ram Gurjar, Mr. Nema; Bhattacharjee, T (Innovational: Journal of Nursing and Healthcare, 2024)
A study was conducted to see the effectiveness of structured teaching programme on prevention of nosocomial infection. Aim: The aim of the study was to assess the knowledge and practice regarding prevention of nosocomial infections among staff nurses. Materials and Methods: Pre-experimental one group pre-test post-test design was used. The study was carried out in NIMS Hospital, Jaipur. 30 staff nurses were conveniently selected for the study. The data collection was done with the help of structured knowledge questionnaire and 3 point Likert Scale on practice regarding prevention of nosocomial infection and it was evaluated by Mean and standard deviation. The statistical method for demographic variables was presented using frequencies and percentages. Mean and standard deviation was used to describe the knowledge and practice of staff. Further statistical significance on the effectiveness of the STP was analyzed using paired “t” test. Association between demographic variables with knowledge and practice score of staff nurses was tested using Chi square test. Results: The study result revealed that the mean post-test knowledge score 19.9 was higher than mean pre-test knowledge score 13.8 .The computed„t‟ value 13.50 (p<0.05) showed that there was significant difference between the mean pre-test and mean post-test knowledge score. The mean post-test practice score was 36.5 higher than mean pre-test practice score 24.3. The computed„t‟ value -7.88 (p<0.05) showed that there was significant difference between the mean pre-test and mean post-test practice score. Conclusion: Study revealed that STP is one of the important teaching tool to improve the knowledge and practice regarding prevention of nosocomial infection among staff nurses which decrease the rate of nosocomial infection in patients.